ANALISIS KELAYAKAN OBJEK WISATA AIR TERJUN SERATAK DI DESA TELUK MESJID KABUPATEN KOTABARU KALIMANTAN SELATAN - Muhammad Fikri Fani Ansori; Khairun Nisa; Asysyifa Asysyifa (Jurnal Sylva Scienteae, 2020)
Seratak’s Waterfall is one of destination located in Desa Teluk Mesjid, Kotabaru. It has 5 meters high and have so many potential such as flora and fauna. This research for analyzed properness the Seratak Waterfall and to know the society’s perceptions. The properness not only for the economic but to know if Seratak Waterfall have potential and can develop as a Tourism Object. The approach method used in this study is a survey research method with quantitative descriptive analysis techniques. The assessment of the potential and tourist attraction of 76,00% indicate that the location of Seratak Waterfall is feasible to be develop as tourism attraction. The society of Desa Teluk Mesjid RT.03 hope for Seratak Waterfall could be develop, and involved in the management. Tourists visiting the Seratak Waterfall hope the government repair the accessibility also the facilities in its development.Keyword: seratak waterfall; feasibility analysis; society perception and tourists perception